Development Of An LC-MS/MS Approach To Detect And Quantify Two Impurities Of Ranolazine (Journal of Pharmaceutical Negative Results, 2023)
In the ranolazine (RLE) synthesis 1-Methoxy-2-(oxiranyl methoxy) benzene (RC-A) and 2-Chloro-N-(2,6-dimethylphenyl) acetamide (RC-B) are generated as an intermediates. The presence of RC-A and RC-B impurities in RLE could potentially affect its effectiveness. The purpose of this investigation was to establish a LC-MS/MS methodology to identify and evaluate RC-A and RC-B impurities in RLE samples. The method for RC-A and RC-B analysis was developed on X-Select CSH C18 column with gradient elution using mobile phase consisted of 0.1% ammonia (mobile phase A) and methanol (mobile phase B). Mass spectrometer with electrospray ionization operated in the MRM mode was used in the analysis of RC-A (m/z181.1→151.1) and RC-B (m/z198.2→107.1). The LC-MS/MS methodology proposed showed a good linearity (0.251 to 1.128 ppm and 0.258 to 1.141 ppm), good system precision (RSD = 0.8% and 2.9%), good method precision (RSD = 1.0% and 1.3%), acceptable accuracy (94.1-106.0% and 96.2-99.2%), low detection limit (0.075 ppm and 0.077 ppm) and low quantitation limit (0.251 ppm and 0.258 ppm) for RC-A and RC-B, respectively. The LC-MS/MS methodology proposed can be utilized to assess the quality of RLE sample for the presence of RC-A and RC-B impurities.